Continuation of pregnancy despite a diagnosis of severe fetal anomaly: a retrospective French study. (10th May 2016) - Madeuf, Amelie; Roman, Horace; Verspyck, Eric
Abstract: Introduction: The aim of this study was to describe diagnoses and outcomes when women choose to continue a pregnancy despite detection of severe fetal anomaly. Material and methods: Retrospective study from a French national registry between 2005 and 2009. Various indication groups were classified based on a scale incorporating mortality and morbidity outcomes. Risk factors for perinatal mortality and predictors of neonatal survival were determined by multinomial logistic regression analyses. Results: The overall number of pregnancies that continued after diagnosis of a severe fetal anomaly was 2266 (6.6%). The diagnoses were categorized into life‐limiting conditions (34.2%), serious disability anomaly (40.8%), potential intellectual disability (8.6%), other conditions (8.8%), and failure to classify (7.4%). During the study period, there was a significant increase in the number of women who continued pregnancy after their fetus was diagnosed with a life‐limiting condition ( p = 0.03), and a decrease when the fetus was diagnosed with potential intellectual disability ( p = 0.01). Pregnancy outcomes were intrauterine fetal death (17.4%), neonatal mortality (22.3%), neonatal survival (52.7%), or unknown (7.5%). Multinomial logistic regression analysis suggested an increased likelihood of neonatal survival among fetuses diagnosed with serious disability anomaly [59.8%, relative risk (RR) 4.1, 95% CI 3.1–5.7], potential intellectual disability (74.4%, RR 11.5, 95% CI 6.2–21.2), and other conditions (80%, RR 12.6, 95% CI 5.7–27.9) compared with life‐limiting conditions (30.1%). Conclusions: An increasing proportion of women chose to continue pregnancy after the fetus was diagnosed with a potentially life‐limiting condition; survival of children with these diagnoses is not uncommon.